2010
DOI: 10.1523/jneurosci.0653-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

EngrailedHomeobox Genes Regulate Establishment of the Cerebellar Afferent Circuit Map

Abstract: The spatial organization of the cerebellar afferent map has remarkable correspondence to two aspects of intrinsic patterning within the cerebellum embodied by a series of lobules and Purkinje cell (PC)-striped gene expression. Using male and female mice, we tested whether the Engrailed (En) homeobox genes are a common genetic substrate regulating all three systems, since they are expressed in spatially restricted domains within the cerebellum and are critical for patterning PC gene expression and foliation. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
139
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(142 citation statements)
references
References 53 publications
3
139
0
Order By: Relevance
“…The Engrailed genes encode homeodomain containing transcription factors that are master regulators of cerebellar patterning (Desplan, Theis, & O'Farrell, 1985; Joyner, Kornberg, Coleman, Cox, & Martin, 1985; Joyner & Martin, 1987; Sillitoe, Stephen, Lao, & Joyner, 2008; Sillitoe, Vogel, & Joyner, 2010). These genes are critical for normal cerebellar development, even after their early role in maintaining Fgf8 expression in the isthmic organizer is complete.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Engrailed genes encode homeodomain containing transcription factors that are master regulators of cerebellar patterning (Desplan, Theis, & O'Farrell, 1985; Joyner, Kornberg, Coleman, Cox, & Martin, 1985; Joyner & Martin, 1987; Sillitoe, Stephen, Lao, & Joyner, 2008; Sillitoe, Vogel, & Joyner, 2010). These genes are critical for normal cerebellar development, even after their early role in maintaining Fgf8 expression in the isthmic organizer is complete.…”
Section: Discussionmentioning
confidence: 99%
“…These genes are critical for normal cerebellar development, even after their early role in maintaining Fgf8 expression in the isthmic organizer is complete. In fact, in later stages of cerebellar development, En1/2 are essential for anterior‐posterior and medial‐lateral patterning of the cerebellum (Cheng et al, 2010; Joyner et al, 1991; Sgaier et al, 2007; Sillitoe et al, 2008; Sillitoe et al, 2010). Interestingly, our recent RNA‐seq analysis of Chd7 ‐deficient cerebellar GCps showed that En1 expression was upregulated in these cells, implicating CHD7 as a potential repressor of En1 expression (Whittaker et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry was carried out as described previously (Reeber et al 2011;Sillitoe et al 2003Sillitoe et al , 2010White and Sillitoe 2013b). Briefly, tissue sections were thoroughly washed, blocked with 10% normal goat serum (NGS; Sigma, St. Louis, MO) for 1 h at room temperature, and then incubated in 0.1M PBS containing 10% NGS, 0.1% Tween-20, and the anti-CAR8 primary antibodies (1:1,000; Santa Cruz Biotechnology, Santa Cruz, CA) for 16 -18 h at room temperature, shaking gently.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, these stripe-like expression domains are coincident with the innervation of cerebellar afferents (mossy and climbing fibers), suggesting that these patterning genes regulate the topographic mapping of axons. Consistent with this possibility, En2 mouse mutants display connectivity phenotypes disrupting the innervation of mossy fibers (Herrup and Kuemerle 1997;Baader, Sanlioglu et al 1998;Baader, Vogel et al 1999;Sillitoe, Stephen et al 2008;Sillitoe, Gopal et al 2009;Sillitoe, Vogel et al 2010). Thus En2 is important in establishing the cerebellar connectivity map during development.…”
Section: En2 Regulates Connectivitymentioning
confidence: 79%